Avaliação do p-cimeno em um modelo experimental de autismo induzido por lipopolissacarídeo em ratos Wistar - Camargo, Rick Wilhiam de (2019)
Introduction: Autism Spectrum Disorder (ADS) is a neuropsychiatric disorder characterized by impairments in reciprocal social interaction, stereotypies, restricted interest, and memory deficits. Maternal immune activation (AIM) in animals exposed to lipopolysaccharide (LPS) on the ninth day and gestational day (GD9,5) is capable of promoting autistic-type sick behavior. New therapeutic alternatives are being sought from medicinal plants in order to ameliorate these symptoms. Among the most diverse alternatives, we highlight p-cymene which has shown positive results in the treatment of neurological and psychiatric diseases. Objective: The objective of this study was to evaluate the effect of chronic treatment of p-cymene on behavioral, memory and its possible modulatory capacity of proinflammatory cytokines in Wistar rats exposed in the prenatal period to LPS. Methods: In order to proceed with AIM, pregnant females of Wistar rats received a single intraperitoneal (i.p.) injection of LPS in GD9,5. Offspring males were characterized with type-autistic symptoms and the saline group received i.p. of 0.9% NaCl (SAL). After weaning the LPS and SAL groups were treated in a chronic manner with the substances: saline, risperidone and p-cymene. Behavioral and memory tests were performed on PND52 and PND53 and proinflammatory cytokines (TNF-α, IL-1β and IL-6) measured in PND54 after death and dissection of the brain structures (prefrontal cortex and hippocampus). Results: LPS administration was able to promote type-autistic symptoms in the offspring. The chronic administration of p-cymene reduced the exploratory locomotor activity and normalized the stereotyped behavior. However, p-cymene did not alter the memory of these animals. Biochemical analyzes performed on the prefrontal cortex and hippocampus revealed that risperidone and p-cymene may be chronically acting proinflammatory. Conclusion: Chronic treatment with p-cymene did not alter the behavior and memory of Wistar rats exposed in the prenatal period to LPS. It is suggested that the proinflammatory effects found through biochemical analyzes may be being promoted by the p-cymene secondary metabolites.